Decomposing the multiple encoding benefit in visual long-term memory: Primary contributions by the number of encoding opportunities. - Tozios, Caitlin J. I.; Fukuda, Keisuke (Memory & Cognition, 2024)
Although access to the seemingly infinite capacity of our visual long-term memory (VLTM) can be restricted by visual working memory (VWM) capacity at encoding and retrieval, access can be improved with repeated encoding. This leads to the multiple encoding benefit (MEB), the finding that VLTM performance improves as the number of opportunities to encode the same information increases over time. However, as the number of encoding opportunities increases, so do other factors such as the number of identical encoded VWM representations and chances to engage in successful retrieval during each opportunity. Thus, across two experiments, we disentangled the contributions of each of these factors to the MEB by having participants encode a varying number of identical objects across multiple encoding opportunities. Along with behavioural data, we also examined two established EEG correlates that track the number of maintained VWM representations, namely the posterior alpha suppression and the negative slow wave. Here, we identified that the primary mechanism behind the MEB was the number of encoding opportunities. That is, recognition memory performance was higher following an increase in the number of encoding opportunities, and this could not be attributed solely to an increase in the number of encoded VWM representations or successful retrieval. Our results thus contribute to the understanding of the fundamental mechanisms behind the influence of VWM on VLTM encoding.